Influence of Erbium Ions on the Optical and Structural Properties of Polyvinyl Alcohol. (27th May 2015) - Hamdalla, Taymour A.; Hanafy, Taha A.; Bekheet, Ashraf E.
Abstract : Polyvinyl alcohol (PVA) films doped with erbium chloride (ErCl3 ) have been prepared by casting from their aqueous solutions. The structure of the doped samples as well as the interactions between the host PVA and Er +3 was investigated using FTIR spectroscopy. The optical measurement was recorded at room temperature in the range from 200 nm to 2000 nm. FTIR measurements revealed that Er +3 forms complex configuration within the PVA structure. PVA doped with 9 wt% of ErCl3 exhibits energy gap and refractive index of 5.1 eV and 1.72, respectively. The effect of the doping increment of ErCl3 on the optical parameters has been discussed.